Postoperative observations in genital prolapse surgery - T. A. Gustovarova; L. S. Kirakosyan; E. E. Feramuzova (Кубанский научный медицинский вестник, 2021)
Background. Pelvic prolapse is a common reason of gynaecological visits. Predispositions of genital prolapse comprise oestrogen deficiency, vaginal labour, congenital connective tissue dysplasia, etc. Specific approaches and treatments for genital prolapse are priority developments in gynaecological surgery.Objectives. Assessment of the safety and efficacy of variant techniques for pelvic prolapse surgical correction depending on its type and clinical manifestations.Methods. A total of 188 women were examined and treated surgically. The patients were divided in three cohorts by type of prolapse. Cohort 1 contained 108 patients with a pronounced defect of pubocervical fascia having mesh implants; cohort 2 — 65 patients without pronounced fascial defect having urethral slings and native-tissue corrections; cohort 3 — 15 prolapse patients having sacrovaginopexy for longer reproductive health.Results. Two complications were observed: 1000-mL blood loss requiring internal iliac arteries ligation and haemotransfusion; 300-mL blood loss with pelvic haematoma opening and drainage. Postoperative period without peculiarities in all cohorts. Two patients developed vaginal mucosal erosion up to 1 cm in one month. One-year clinical monitoring in all cohorts showed an improvement in functional and anatomical outcomes.Conclusion. Genital prolapse requires a personalised approach, which contributes to patient compliance and reduces postoperative complications and recurrences. Mesh implants improve surgical outcomes in patients with severe defects of pubocervical fascia, and urethral slings are effective in urinary incontinence.